Semi-Synthetic Ecdysteroid 6-Oxime Derivatives of 20-Hydroxyecdysone Possess Anti-Cryptococcal Activity - Szerencsés, Bettina; Vörös, Mónika; Bagi, Kristóf; Háznagy, Márton B.; Hunyadi, Attila; Vágvölgyi, Csaba; Pfeiffer, Ilona; Vágvölgyi, Máté (Microbiology research, 2022)
Cryptococcosis, a life-threatening fungal infection, frequently occurs in patients suffering from AIDS. The treatment of the disease is hampered by the limited number of the effective drugs and the increasing resistance; therefore, to find new active substances is needed. As meningitis is the most serious infection affecting the AIDS patients, effective drugs have to be capable of entering to the central nervous system. Ecdysteroids are natural bioactive molecules with considerable anabolic activity and without toxic side effects on humans. The aim of this work was to study the anti-cryptococcal activity of a natural ecdysteroid, 20E, and its three semi-synthetic derivatives obtained by structural modification of the original molecule. We established the minimum inhibitory concentration of the compounds with microdilution method and demonstrated their fungicidal activity by flow cytometry and cultivation of the drug-treated cells. The interaction of the compounds with each other and efflux transporter inhibitors was assessed by checkerboard titration method. Two derivatives, 20E-EOx and 20E-ZOx, inhibited the growth of Cryptococcus neoformans with minimum inhibitory concentration 2 mg/mL and 1 mg/mL, respectively; both compounds possess fungicidal effect. A combination of the ecdysteroids with each other and verapamil resulted in additive interaction. This study confirmed that structural modification of an originally non-antimicrobial molecule can enhance its effectiveness.